(untitled) (Research, Society and Development, 2022)
Introduction: Ameloblastoma is a benign neoplasm characterized by its slow, asymptomatic and aggressive growth. It affects the bones of the maxillomandibular complex, mainly in the region of the body and mandibular ramus. Less than 2% of cases occur in children younger than 10 years. Objective: to discuss multicystic ameloblastoma in the mandible in view of the necessary care for a good postoperative period. Methodology: This study was prepared through bibliographical research on Pubmed, Ncbi, Google academic and scielo platforms. Articles published in English between 2016 and 2022 and attached to these platforms were searched. The descriptors were used: Ameloblastoma; Therapy; Jaw. Discussion: The treatment of ameloblastoma consists of the application of conservative or radical surgical techniques. Authors investigated a conservative versus radical approach to the treatment of onlyread/Multicistic through a literature review. They found that conservative treatment with marsupilization to reduce the lesion, enucleation, curettage and finalization with Carnoy’s solution has a lower rate of side effects. Depending on multifactors, the patient may have a 60% to 90% chance of recurrence. Reasons for recurrence after a radical approach may be multifactorial, such as stump debris, soft tissue, or intraoperative contamination. Radical surgeries require care that must be followed strictly, as there are possibilities of serious complications. Conclusion: The posterior region of the mandible is the most affected site and there is no gender predilection. Most cases are asymptomatic and detected on routine radiographs. Attempts to remove the tumor by curettage presumably leave behind small islands of tumor within the bone, which is later determined to be recurrent disease.